Site-specific substitution in atomically precise carboranethiol-protected nanoclusters and concomitant changes in electronic properties - Vivek Yadav; Arijit Jana; Swetashree Acharya; Sami Malola; Harshita Nagar; Ankit Sharma; Amoghavarsha Ramachandra Kini; Sudhadevi Antharjanam; Jan Machacek; Kumaran Nair Valsala Devi Adarsh; Tomas Base; Hannu Häkkinen; et al. (Nature Communications)
Abstract We report the synthesis of [Ag17(o 1-CBT)12]3- abbreviated as Ag17, a stable 8e⁻ anionic cluster with a unique Ag@Ag12@Ag4 core-shell structure, where o 1-CBT is ortho-carborane-1-thiol. By substituting Ag atoms with Au and/or Cu at specific sites we created isostructural clusters [AuAg16(o 1-CBT)12]3- (AuAg16), [Ag13Cu4(o 1-CBT)12]3- (Ag13Cu4) and [AuAg12Cu4(o 1-CBT)12]3- (AuAg12Cu4). These substitutions make systematic modulation of their structural and electronic properties. We show that Au preferentially occupies the core, while Cu localizes in the tetrahedral shell, influencing stability and structural diversity of the clusters. The band gap expands systematically (2.09 eV for Ag17 to 2.28 eV for AuAg12Cu4), altering optical absorption and emission. Ultrafast optical measurements reveal longer excited-state lifetimes for Cu-containing clusters, highlighting the effect of heteroatom incorporation. These results demonstrate a tunable platform for designing nanoclusters with tailored electronic properties, with implications for optoelectronics and catalysis.